Mapping of high-risk detection of women pregnancy on antenatal care in Talise Health Center, Palu City, Indonesia - Muhammad Asep Dwitama; Masni; Rosmala Nur; Apik Indarty; Muh Tahir A; Anwar Mallongi; Muhammad Basir; Mahfudz; Alam Ansyari (Elsevier, 2021)
Objective: This study aimed to map pregnant women with high-risk pregnancies based on age, parity, pregnancy history, childbirth history, illness history, and CED status history as well as the relationship between the six factors. Method: This study utilized a survey method with descriptive data without the intervention of variables but observed phenomena or sought the relationship between phenomena and other variables. The survey was conducted with an approach using Geographic Information Systems (GIS). There were 243 respondents obtained using the Lemeshow formula, while the data were analyzed using spatial techniques and Chi-Square test with p > 0.05. Results: The results of spatial analysis using a 1: 50,000 scale map showed that; (1) high-risk and very high-risk pregnancies dominated Talise, (2) based on age, parity, pregnancy history, childbirth history, illness history, and CED status, cases of high-risk pregnancies were all detected in Talise, (3) age (p = 0.000). Furthermore, pregnancy history (p = 0.004) correlated with a high-risk pregnancy. Besides, parity, childbirth history, illness history, and CED status did not correlate with high-risk pregnancy since the p-value > 0.05; (4) age and pregnancy history influenced the high-risk pregnancy.